A non-symmetrical-component approach to the analysis of unbalanced network under fault conditions - He, Wu Xian. (2010)
This research project is focused on the alternative approach in the formulation for unbalanced fault current calculation without using symmetrical component. The formulation of the system equation and the solution algorithm by the elimination method is reviewed and tested. A new compensation method is proposed and developed. Based on the review of various papers on phase-co-ordinate method, each element in the power system, such as generator, transformer, transmission line, cable and motor can be represented by an equivalent admittance matrix. The system equation can be formulated by appropriately assembling all the element admittance matrices.